Do conhecimento tradicional ao princípio ativo: dilemas sociais da atividade de pesquisa etnofarmacológica - Almeida, Marcelo Fetz de (2008)
The Research and Development (R&D) in ethnopharmacology and etnobiology fields, guided by the therapeutic information obtained with local communities and indigenous people, holders of traditional knowledge, produces social conflicts and social disputes. Firstly, it is a paradoxical scientific activity since the modern scientific discovery in ethnopharmacology is produced by a non-scientific knowledge. This controversial research strategy intends to produce a socially legitimized knowledge through a process of epistemic standardization. Secondly, although the use of traditional knowledge is a typical activity, to access it and to use it requires the signature of a contract for the equitable sharing of benefits as well as the signature of a term of prior consent access. These two juridical requirements are at the same time a new ethical parameter in scientific research and a barrier to the autonomy of the scientific field. Therefore, through the politic action scientists and researches seeks new social strategies to recovery the autonomy of the scientific field in ethnopharmacology and ethnobiology areas. Thus, this sociological research analyzes the internal conflicts between scientists in the scientific field through the examination of the social controversies in the use of two distinct research models, the vertical and the horizontal research models, as well as the examination of the external social disputes of the scientific activity, specially the politic action of scientists concerning to the autonomy question. In this research, the question of access, use and equitable sharing of benefits in R&D processes emerges as an interesting strategy used by scientists to legitimate the appropriation of the traditional knowledge. As non-knowledge, the traditional knowledge is transformed by the modern commercial science in generic information without significance. At the same time, this traditional generic information would be liable to be manipulated and appropriated by pharmaceutical multinationals trough the application of intellectual property rights. Finally, the appropriation of the traditional communities claim intends to legitimate socially the controversial scientific activity of ethnopharmacologists, ethnobiologists and pharmaceutical industries.